GROWTH RESPONSE OF UNGU EGGPLANT (Solanum melongena L.) TO ORGANIC WATER Hyacinth (Eichhornia crassipes) AND NPK PUPPY DOSAGE CHARGE - Murjiono, Mohammad Andi; Supriyo, Hadi; Ariyanto, Shodiq Eko (Muria Jurnal Agroteknologi (MJ-Agroteknologi), 2023)
Tanaman terong sangat berpotensi untuk dibudidayakan dalam rangka untuk memenuhi kebutuhan sayuran. Pada sisi lain, masalah kesuburan lahan menjadi kendala dalam budidaya terong. Pengunaan pupuk pupuk organik enceng gondok dan pupuk NPK merupakan upaya mengembalikan tingkat kualitas tanah yang digunakan dalam budidaya tanaman pertanian. Tujuan penelitian untuk mengetahui respon pertumbuhan terong ungu (Solanum melongena L.) terhadap pengaruh pemberian pupuk organik eceng gondok (Eichhornia crassipes) dan dosis pupuk NPK. penelitian dilaksanakan di Desa Cengkal Sewu, Kecamatan Sukolilo, Kabupaten Pati pada bulan Mei sampai Juli 2022. Percobaan faktorial berpola dasar Rancangan Acak Kelompok Lengkap (RAKL) yang terdiri atas dua faktor dan tiga ulangan. Faktor pertama adalah dosis pupuk organik eceng gondok (E), terbagi dalam tiga taraf yaitu E1 (10 ton/ha), E2 (20 ton/ha) dan E3 (30 ton/ha). Faktor ke dua adalah dosis pupuk majemuk NPK (N) yang terdiri dari tiga taraf yaitu N1 (100 kg/ha), N2 (200 kg/ha) dan N3 (300 kg/ha). Hasil akhir menunjukkan bahwa dosis pupuk organik eceng gandok berpengaruh nyata pada pertumbuhan tanaman terong ungu yaitu pada tinggi tanaman terong ungu umur 4 MST. Dosis pupuk organik eceng gondok 10 ton/ha meningkatkan tinggi tanaman terong ungu umur 4 Minggu setelah tanam. Dosis pupuk majemuk NPK berpengaruh nyata terhadap parameter pertumbuhan. Dosis pupuk majemuk NPK 200 kg/ha meningkatkan pertumbuhan tanaman terong ungu. Terdapat interaksi antara dosis pupuk organik eceng gondok dengan dosis pupuk majemuk NPK terhadap bobot kering tajuk tanaman terong ungu. Eggplant plants have the potential to be cultivated in order to fulfill vegetable needs. On the other hand, land fertility problems are an obstacle in eggplant cultivation. The use of water hyacinth organic fertilizer and NPK fertilizer is an effort to restore the level of soil quality used in the cultivation of agricultural crops. The purpose of the study was to determine the growth response of purple eggplant (Solanum melongena L.) to the effect of water hyacinth organic fertilizer (Eichhornia crassipes) and NPK fertilizer doses. The research was conducted in Cengkal Sewu Village, Sukolilo District, Pati Regency from May to July 2022. The factorial experiment was patterned on the basis of a Completely Randomized Group Design (CRGD) consisting of two factors and three replications. The first factor is the dose of water hyacinth organic fertilizer (E), divided into three levels, namely E1 (10 tons/ha), E2 (20 tons/ha) and E3 (30 tons/ha). The second factor is the dose of NPK compound fertilizer (N) which consists of three levels namely N1 (100 kg/ha), N2 (200 kg/ha) and N3 (300 kg/ha). The final results showed that the dose of water hyacinth organic fertilizer had a significant effect on the growth of purple eggplant plants, namely the height of purple eggplant plants at the age of 4 weeks after planting. The dose of water hyacinth organic fertilizer 10 tons/ha increased the height of purple eggplant plants at 4 weeks after planting. The dose of NPK compound fertilizer has a significant effect on growth parameters. The dose of NPK compound fertilizer 200 kg/ha increases the growth of purple eggplant plants. There is an interaction between the dose of water hyacinth organic fertilizer and the dose of NPK compound fertilizer on the crown dry weight of purple eggplant plants.